2019
DOI: 10.1016/j.jjcc.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage occlusion using LAmbre Amulet and Watchman in atrial fibrillation

Abstract: A B S T R A C TBackground: Left atrial appendage closure (LAAC) has been suggested as an alternative to anticoagulation in non-valvular atrial fibrillation (AF). The present study aimed to compare a LAmbre LAA occluder system [Lifetech Scientific (Shenzhen) Co. Ltd., Shenzhen, China] with the most investigated Amulet (St. Jude Medical Inc., St. Paul, MN, USA) and Watchman (Boston Scientific, Plymouth, MN, USA) devices in terms of peri-procedural and short-term outcomes. Methods: This is a prospective observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 17 publications
4
44
1
3
Order By: Relevance
“…The rate for ischemic stroke only in the LAmbre group was respectively 2.7 events per 100 patient‐years, resulting in a 60% risk reduction for stroke, compared with the expected stroke rate with a mean CHA 2 DS 2 ‐VASc score of 4.8 (expected rate of 6.7 events per 100 patient‐years 28 ). All other LAmbre registries with shorter follow‐up times from 6 to 12 months observed low rates of ischemic stroke (0%, 15–17 1.3% 12 ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The rate for ischemic stroke only in the LAmbre group was respectively 2.7 events per 100 patient‐years, resulting in a 60% risk reduction for stroke, compared with the expected stroke rate with a mean CHA 2 DS 2 ‐VASc score of 4.8 (expected rate of 6.7 events per 100 patient‐years 28 ). All other LAmbre registries with shorter follow‐up times from 6 to 12 months observed low rates of ischemic stroke (0%, 15–17 1.3% 12 ).…”
Section: Discussionmentioning
confidence: 88%
“…Small registry studies showed high implant success rates and acceptable periprocedural complication rates, as well as favorable short‐term clinical outcomes of the LAmbre device 12–16 . Another head‐to‐head comparison demonstrated comparable peri‐procedural and clinical outcomes for up to 6 months for LAmbre, Amulet, and Watchman 17 . Currently, a 3‐year global post‐market surveillance study investigates the performance of the LAmbre device in 500 participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 publications included in the data analysis of this systematic review were published from 2016 until 2019 [9,[14][15][16][17][18][19][20][21][22]. The reported total cohort in these 10 publications comprised n = 403 NVAF patients, treated with implantation of a LAmbre™ device.…”
Section: Resultsmentioning
confidence: 99%
“…DAPT Dual antiplatelet therapy (aspirin plus clopidogrel) LMWH Low-molecular weight heparin N/A Not available NOAC New oral anticoagulants OAC Oral anticoagulation SAPT Single antiplatelet therapy (aspirin or clopidogrel) VKA Vitamin K antagonistsTable 4 Pre-and postprocedural regimens, complications and outcomes Major procedure-related complications (n= / %) Minor procedurerelated complications (n= / %) Follow up time / Outcome (AE) (n= / %) Chen et al (2019)[21] Total: n = 0 / 0% 0% 6 months: Total: n = 0 / 0%; Stroke/TIA: n = 0 / 0%; TFD: n = 0 / 0%; RF > 5 mm: n = 0 / 0%; Major Bleeding: n = 0 / 0%; Device embolization: n = 0 / 0% RF < 5 mm: n = 9 / 30.0%; Minor Bleeding: n = 0 / 0%Feng et al (2019) [22] Total: n = 1 / 5.9%; Death: n = 0 / 0%; PerTam: n = 1 / 5.9% n = 2 / 11.8% (haematoma) 12 months: Total: n = 0 / 0%; Stroke/TIA: n = 0 / 0%; TFD: n = 0 / 0%; RF > 5 mm: n = 0 / 0%; Major Bleeding: n = 0 / 0%; Device embolization: n = 0 / 0% RF < 5 mm: n = 2 / 11.8%; Minor Bleeding: n = 0 / 0%; n = 1 / 5.9% sudden cardiac death at 545 days Reinsch et al (2018) [19] Total: n = 0 / 0%; Death: n = 0 / 0% 0% 6 months: Total: n = 0 / 0%; Stroke/TIA: 0%; TFD: 0%; RF > 5 mm: 0%; Major Bleeding: n = 0 / 0%; Device embolization: n = 0 / 0% RF < 5 mm: 0%; Minor Bleeding: n = 0 / 0% Park et al (2018) [18] Total: n = 4 / 6.7%; Death: n = 1 / 1.7%; PerTam: n = 3 / 5.0%; PerTam requiring surgery with fatal outcome: n = 1 / 1.7%; Pseudoaneurysm of right AFC requiring surgical repair: n = 1 / 1.7% 0% 12 months: Total: n = 5 / 6.7%; Stroke/TIA: n = 2 / 1.6%; TFD: 0%; RF > 5 mm: n = 3 / 5% a ; Major bleeding: 0%; Device embolization: n = 0 / 0% RF < 5 mm: n = 14 / 24.6%; Minor bleeding: n = 5 / 5% Death unrelated to LAAC: 3% Kleinecke et al (2018) [17] Total: n = 0 / 0%; Death: n = 0 . (2017) [15] Total: n = 5 / 3.3%; Death: n = 0 / 0%; PerTam: n = 2 / 1.3; Stroke: n = 1 / 0.7%; Major bleeding: n = 1 / 0.7% n = 4 / 2.6% (Femoral hematoma: n = 2; Arteriovenous fistula: n = 1 Pseudoaneurysm; n = 1)12 months: Total: n = 5 / 3.9%; Stroke: n = 3 / 2.0%; TFD: n = 2 / 1.3%; RF > 5 mm: 0%; Major Bleeding: n = 0 / 0%; Device embolization: n = 0 / 0% Death unrelated to LAAC: n = 1 / 1.3% Available TEE at 12 months: n = 121…”
mentioning
confidence: 99%